New Insights Into the Role of Seed Oil Body Proteins in Metabolism and Plant Development - Shao, Qun; Liu, Xiaofan; Su, Tong; Ma, Changle; Wang, Pingping (Frontiers in Plant Science, 2019)
Oil bodies (OBs) are ubiquitous dynamic organelles found in plant seeds. They have attracted increasing attention recently because of their important roles in plant physiology. First, the neutral lipids stored within these organelles serve as an initial, essential source of energy and carbon for seed germination and post-germinative growth of the seedlings. Secondly, they are involved in many other cellular processes such as stress responses, lipid metabolism, organ development and hormone signaling. The biological functions of seed OBs are dependent on structural proteins, principally oleosins, caleosins and steroleosins, which are embedded in the OB phospholipid monolayer. Oleosin and caleosin proteins are specific to plants and mainly act as OB structural proteins and are important for the biogenesis, stability and dynamics of the organelle; whereas, steroleosin proteins are also present in mammals and play an important role in steroid hormone metabolism and signaling. Significant progress using new genetic, biochemical and imaging technologies has uncovered the roles of these proteins. Here, we review recent work on the structural or metabolic roles of these proteins in OB biogenesis, stabilization and degradation, lipid homeostasis and mobilization, hormone signal transduction, stress defenses and various aspects of plant growth and development.